Long working hours and psychiatric treatment: A Danish follow-up study - Harald Hannerz; Karen Albertsen; Martin Lindhardt Nielsen; Anne Helene Garde (Nordic Association of Occupational Safety and Health (NOROSH), 2021)
OBJECTIVE: This study aimed to estimate prospective associations between long working hours and (i) redeemed prescriptions for psychotropic drugs and (ii) psychiatric hospital treatment due to mood, anxiety or stress-related disease, among full-time employees in Denmark. METHODS: Full-time employees who participated in the Danish Labor Force Survey sometime in the period 2000-2013 (N=131 321] were followed for up to five years in national registers for redeemed prescriptions for psychotropic drugs and psychiatric hospital treatment due to mood, anxiety or stress-related disease. Rate ratios (RR) were estimated for 41-48 versus 32-40 and >48 versus 32-40 working hours a week. The analyses were controlled for sex, age, night shift work, calendar time of the interview and socioeconomic status (SES). Prevalent cases were excluded in primary analyses. RESULTS: The RR for psychotropic drugs were estimated at 0.94 [99% confidence interval (CI) 0.88-1.01] for 41-48 versus 32-40 working hours a week and 1.08 (99% CI 0.99-1.18) for >48 versus 32-40 working hours a week. The corresponding RR for psychiatric hospital treatments were estimated at 0.90 (95% CI 0.75-1.08) and 0.96 (95% CI 0.76-1.21). We did not find any statistically significant interaction between weekly working hours and age, sex, SES or night shift work. CONCLUSION: Long working hours as they occur in in the general working population of Denmark are not an important predictor of mental ill health.